2017
DOI: 10.1186/s12885-017-3355-9
|View full text |Cite
|
Sign up to set email alerts
|

The unique C- and N-terminal sequences of Metallothionein isoform 3 mediate growth inhibition and Vectorial active transport in MCF-7 cells

Abstract: BackgroundThe 3rd isoform of the metallothionein (MT3) gene family has been shown to be overexpressed in most ductal breast cancers. A previous study has shown that the stable transfection of MCF-7 cells with the MT3 gene inhibits cell growth. The goal of the present study was to determine the role of the unique C-terminal and N-terminal sequences of MT3 on phenotypic properties and gene expression profiles of MCF-7 cells.MethodsMCF-7 cells were transfected with various metallothionein gene constructs which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…For example, MT3 gene knock out showed an effect on post-radiation induced survival of glioma cells [ 87 ]. In MCF-7 cells, a breast cancer cell line, the C- and N-terminal of MT3 contributed to the growth inhibition of cancer cells [ 88 ]. Furthermore, MTs expression level or polymorphisms are used to diagnose risks of various cancers such as gastric cancer, colorectal cancer, breast cancer, and hematological malignancies, or to predict cancer progression [ 89 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, MT3 gene knock out showed an effect on post-radiation induced survival of glioma cells [ 87 ]. In MCF-7 cells, a breast cancer cell line, the C- and N-terminal of MT3 contributed to the growth inhibition of cancer cells [ 88 ]. Furthermore, MTs expression level or polymorphisms are used to diagnose risks of various cancers such as gastric cancer, colorectal cancer, breast cancer, and hematological malignancies, or to predict cancer progression [ 89 ].…”
Section: Introductionmentioning
confidence: 99%
“…The finding that the unique C-terminal sequence of MT-3 can promote vectorial active transport when inserted into the MT-1E gene is not a unique finding for renal HK-2 cells. The stable transfection of MT-1E containing the unique C-terminal sequence of MT-3 into MCF-7, a breast cancer cell line, has also been shown to induce dome formation in the stable transformants [ 68 ]. Together these findings suggest that the unique C-terminal insert of MT-3 allows an interaction to be formed with β-actin, myosin-9, and tropomyosin 3 and that this promotes vectorial active transport and an increase in the differentiated function of the epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…This makes MT3 a unique member of MTs family. Recently, expression of MT3-encoding mRNA MT3 has been associated with a worse prognosis of breast cancer and neuroblastoma patients, and it has also been shown that MT3 expression tightly correlates with the poor outcomes of chemotherapy [25][26][27]. However, the role of MT3 in HCC remains unknown.…”
Section: Introductionmentioning
confidence: 99%